Save and grow : a policymaker's guide to the sustainable intensification of smallholder crop production (FAO RomeIT, 2011)
Presents a new paradigm : sustainable crop production intensification which produces more from the same area of land while conserving resources, reducing impacts on the environment and enhancing natural capital and the flow of ecosystem services.
Keywords: CROPS